APROXIMACIÓN A LA ESTRUCTURACIÓN DE CREENCIAS SUPREMACISTAS CONTEMPORÁNEAS - Barradas, Andrés Roberto (2018)
This article intends to make a reflection, based on a bibliographic argument, about how the media could have a clear impact on the generation, development, and even return of supremacist ideological beliefs, not only in its followers, but also, in the community in general, constituting the beliefs that nowadays are being used to argue behaviors of segregation, rejection and discrimination towards the minority groups.